Pengetahuan Masyarakat Penghuni Gunung Kemukus Tentang Pencegahan HIV-AIDS Di Kabupaten Sragen - Dwi Sulistyowati (Poltekkes Kemenkes Surakarta, 2016)
Abstract: Commercial Sex Workers, Knowledge, HIV-AIDS Prevention Efforts. The number of HIV-AIDS sufferers in Indonesia continues to increase and most productive attacking a young age. Health care workers interview results in Hospital SoeratnoGemolong in October 2014, there were 25 HIV-positive AIDS, largely affected by HIV-AIDS is not a native districts Miri Sragen. To analyze the mountain commercial sex workers kemukus knowledge about HIV-AIDS on HIV-AIDS prevention. The study design was observational analytic, using a cross-sectional approach in which to make observations and measurements only once when the measurement variables were analyzed with the model Kai squared test (Chi-Square) to analyze the relationship between one or more independent variables with the dependent variable category. The result of statistical test analysis Fisher's exact Test the relationship between knowledge of HIV-AIDS prevention efforts gained value P-Value: 0.005> 0.001. HIV-AIDS prevention at the commercial sex workers in Mount Kemukus significant associated with HIV-AIDS knowledge